Refleksi Teologi Kovenan Berdasarkan Kejadian 1-3 dan Implikasinya bagi Kehidupan Orang Percaya Masa Kini - Yosua Budi Ristiono; Junio Richson Sirait (Sekolah Tinggi Teologi Kadesi Bogor, 2021)
Covenant theology is one of the most important parts of the Christian faith. Theology is God's initiative in persuading His love for man. God promises to give redemption to all men without requirement. However, advances in technology and science have harmed one's belief in God's promise. The purpose of this study was to find reflections of covenant theology found in Genesis 1-3 and its implications for today's believers. The method used in this article is library research with a descriptive qualitative approach. Through the research of the library, three covenants that God gave to man were covenants of work, redemption, and grace. The covenant can still be enjoyed by all believers today if, it can place Christ at the center of the fulfillment of god's covenant.